NeuralDome: A Neural Modeling Pipeline on Multi-View Human-Object Interactions - Zhang, Juze; Luo, Haimin; Yang, Hongdi; Xu, Xinru; Wu, Qianyang; Shi, Ye; Yu, Jingyi; Xu, Lan; Wang, Jingya (Proceedings (IEEE Computer Society Conference on Computer Vision and Pattern Recognition. Online), 2023)
Humans constantly interact with objects in daily life tasks. Capturing such processes and subsequently conducting visual inferences from a fixed viewpoint suffers from occlusions, shape and texture ambiguities, motions, etc. To mitigate the problem, it is essential to build a training dataset that captures free-viewpoint interactions. We construct a dense multi-view dome to acquire a complex human object interaction dataset, named HODome, that consists of ~71 M frames on 10 subjects interacting with 23 objects. To process the HODome dataset, we develop NeuralDome, a layer-wise neural processing pipeline tailored for multi-view video inputs to conduct accurate tracking, geometry reconstruction and free-view rendering, for both human subjects and objects. Extensive experiments on the HODome dataset demonstrate the effectiveness of NeuralDome on a variety of inference, modeling, and rendering tasks. Both the dataset and the NeuralDome tools will be disseminated to the community for further development, which can be found at https://juzezhang.github.io/NeuralDome